(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
The therapeutic efficacy of medicinal plants is attributed to polyphenolic chemicals, which are essential bioactive components. The bark of the mango plant, Mangifera indica, is a rich source of polyphenols that have antibacterial, anti-inflammatory, and antioxidant properties. For plant-derived products to be consistent, effective, and quality controlled, however, thorough phytochemical standardisation is necessary. The purpose of this research is to provide a comprehensive phytochemical profile by utilising High-Performance Liquid Chromatography (HPLC) and Liquid Chromatography-Mass Spectrometry (LC-MS) to analyse and interpret the polyphenolic content of Mangifera indica bark powder.Mangifera indica bark powder methanolic extracts were made and then separated chromatographically using HPLC in conjunction with photodiode array (PDA) detection. Acetonitrile and aqueous formic acid were used as the mobile phase in a gradient elution technique using a reverse-phase C18 column. Major polyphenolic components, such as Mangifera, quercetin, gallic acid, catechin, and ellagic acid, were identified and quantified using standard reference compounds using UV detection at 280 nm. The structural identity and fragmentation patterns of the identified polyphenols were further confirmed by LC-MS analysis.According to the study,Mangifera is the main component of Mangifera indica bark, which is a strong source of polyphenolic chemicals. Researchers studied the pharmacognostic characteristics of Mangifera indica’s bark. Organoleptic studies of the air-dried bark powdered rind revealed character like brown colour, sweet odour and unique flavour taste. The physiochemical characteristics, which include drying loss, values for total ash, acid-insoluble ash, water-soluble ash, swelling index, and foaming index, were analyzed. Investigate the solubility and extractive value of various solvents, such as methanol, ethanol, hydroalcohol, ethyl acetate, petroleum spirit, water and hexane. The ethanol solvent was found to have a higher extractive value. Flavonoids were found in the aqueous extract according to a preliminary phytochemical investigation.